Traditional Chinese medicine: Its growing potential in treating neurological disorders - Bharat Bhushan; Niraj Kumar Singh; Rajesh Singh (Elsevier, 2024)
Introduction: Neurological diseases are significant challenges to global healthcare systems, demanding innovative and effective therapeutic approaches. Traditional Chinese medicine has emerged as a promising adjunct or alternative in the treatment of various neurological disorders. Methods: Relevant articles were searched using electronic search platforms such as PubMed, Web of Science Google, Scholar, and Scopus" from August 2023 to October 2023. Research and review articles were searched using the keywords such as "Depression", "Brain injury", "Brain-related disorder", "Neurological disorder", "Insomnia" "Ischemic Stroke", "Alzheimer's Disease", "Parkinson's disease", Cerebral Ischemia" paired with "Traditional Chinese Medicine" for the last fifteen years. Critical analysis was performed to identify the appropriate articles after that information was extracted and retrieved. Results: In recent years, scientific research has been activated to unravel the neuroprotective and therapeutic mechanisms underlying Traditional Chinese Medicine interventions. Herbal plants, such as Huperzia serrata, and Ginkgo biloba demonstrated potential in enhancing cognitive function and mitigating symptoms in conditions like Alzheimer's disease, and Parkinson's disease. Acupuncture, through its influence on neural pathways and neurochemical signaling, has shown promise in alleviating pain associated with neurological disorders and improving motor function in conditions like Parkinson's disease. Furthermore, Traditional Chinese Medicine shows therapeutic potential in the treatment of various patients suffering from brain-related diseases. Discussion: Traditional Chinese Medicines play a significant role in the treatment of neurological diseases. An approach to neurological treatment that is more thorough and patient-centered may be accomplished by incorporating the holistic principles of Traditional Chinese Medicine and integrating them with contemporary medical procedures. In the field of neurological diseases, further investigation and cooperation between the Western and traditional medicine communities could bring new therapeutic innovations.